Estimating Long-Run Incarceration Rates for Australia, Canada, England & Wales, New Zealand and the United States - Andrew Leigh (Center for Economic Studies and ifo Institute (CESifo), 2020)
Compiling data from dozens of archival sources, I compile the most extensive series to date of the long-run imprisonment rate for five English-speaking nations: Australia, Canada, England and Wales, New Zealand and the United States. These series are constructed as a share of adults rather than the entire population, and I discuss why the latter can be misleading. In the late-nineteenth century, Australia had the highest incarceration rate of these nations. Today, the United States has the highest rate. With the exception of Canada, incarceration rates have risen markedly since the mid-1980s. These new series are made available in full, to allow other researchers to explore the consequences and causes of incarceration.
Keywords: I30; K14; N30; 330; prison; jail; incarceration; crime